PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN MASYARAKAT PADA PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KANTOR KECAMATAN PARENGGEAN - Dyna Noraini (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2021)
This research discusses how service quality, which is one of the keys to success provided by the government, is related to community satisfaction. The purpose of this study was to determine and analyze the effect of service quality on the level of community satisfaction in the District Integrated Administration Service at the Parenggean District Office. The research method used is a quantitative method with a sample of 100 people. The data obtained from the research results in the form of answers to questionnaires were tested using the validity test then analyzed using simple linear analysis then the t test to determine the level of significance. This analysis is assisted by the SPSS version 18 program. The measurement uses a questionnaire with indicators of service quality and community satisfaction which is distributed to respondents based on the respondent's own experience consisting of 28 questions. Based on the results that have been obtained, the researcher concludes that community satisfaction related to this study is strongly influenced by the quality of service with a value of 66%, this is considered quite influential, but there are still 34% which are still influenced by other variables outside of this study.